Geomorphology : A systematic analysis of late cenozoic landforms - Bloom, Arthur L (New Delhi : Rawat Publications, 1998)
Geomorphology was written for students who have taken at least one introductory course in geology or physical geography. Appropriate intermediate level courses in geomorphology, process geomorphology, or landforms, offered in geoscience, geography, or environmental science departments.A systematic analysis of landforms of the late Cenzoic Era that fully covers the constructional processes of tectonism and volcanism and the erosional processes of weathering, fluvial erosion, glaciers, winds, and waves. It explains each set of processes and the resulting landforms in a separate chapter to provide a comprehensive overview of the subject.
Author Index 461-472p.; Subject Index 473-482p.; Reprint 2012.
Keywords: Glacial geomorphology; Landscape evolution; Volcanoes